TINJAUAN YURIDIS HAK IMUNITAS PEJABAT NEGARA DALAM PENANGANAN PANDEMI COVID SEBAGAI ASPEK KRIMINOGEN TINDAK PIDANA KORUPSI - Muhammad, Tio Aldino; Rusdiana, Emmilia (NOVUM : JURNAL HUKUM, 2021)
The national legal policy has determined that Indonesia is a country that adheres to the Rule of Law system, as regulated in Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (hereinafter referred to as the 1945 Constitution). Mandated in Article 1 paragraph (3) Chapter I, the Third Amendment of the 1945 Constitution which returns that "the State of Indonesia is a State of Law". This means that the Unitary State of the Republic of Indonesia is a country based on law (rechtsstaat), not based on power (machtstaat), and its government is based on a constitutional system (basic law), not absolutism (unlimited power). This research has objectives it aims to describe the position of the Immunity Rights of State Officials in the legal system in Indonesia so that there is legal certainty in its application. Secondly, to analyze the affirmation of the right to immunity in the PERPPU clause No.1 of 2020 which has implications as a criminogenic aspect of corruption. In this study, choosing the type of normative law research (normative law research) or doctrinaire. The approach taken includes a legal review of the law (statute approach) to describe legal facts and provide a prescription that can explain the legal rules contained in PERPPU No.1 of 2020 Article 27 which is questioned because it has an impact as a criminogenic aspect of the occurrence of criminal acts corruption